"Missing and Missed": Failures of the Bruce McArthur Investigation and the Ongoing Victimization of Toronto's Rainbow Streets. Issue 1 (4th March 2022) - Bragagnolo, V.
Abstract: This article analyzes "Missing and Missed: Report of The Independent Civilian Review into Missing Person Investigations, " a review of Toronto Police's conduct during "missing persons" investigations. Analyzing the Bruce McArthur investigation and police's failed efforts to solve some of his victims' "missing persons" cases, questions if overt bias or intentional discrimination influenced police procedure are answered. Critical of blanket statements that pardon police wrongdoing, this article explores the report's recommendations and concludes with a suggestion of a crime prevention model to be considered by Toronto Police who are expected to release a plan of implementation in or before April 2022.